Analysis of some chemical methods for determination of penicillins - Cheng, Wing Hung E.; Santos, Rizalina B. (Manila College of Pharmacy, University of the Philippines, 1987)
As pure crystalline penicillin is available, many chemical methods can be applied accurately. Since then, some titrimetric procedures have been proposed, and followed by those instrumental methods including spectrophotometry, fluorimetry, and colorimetry.
In this thesis, the USP proposed iodometric procedure is studied using Penicillin V Potassium. This method gives quite consistent results for both standard and pentacillin. However, this method is widely criticized for its prominent errors. Another titrimetric method studied is stability-indicating method which gives very satisfactory results for determination of acid-stable penicillins, it serves as a quite simple method when other instrumental methods are not available.
UV spectrophotometry makes use of the inactivation product of penicillin by acid, and the stabilized by mercuric ion, has claimed to be an accurate method. The color product due to the reaction between Penicillin V and concentrated sulfuric acid has been found to be stable in particular temperature. This property is made use of in a colorimetry method. However, the mechanism of this reaction is not known, and further study is necessary.
The reactions between the halogenfluorescein-mercury compounds such as mercurochrome, and penicillin V are involved in the determination of the penicillins by fluorimetric method. The fluorescence intensity of the mercurochrome solution was quenched by the penicillin. The detection limit of penicillin such as ampicillin was 0.8 mcg/ml and calibration curve was rectilinear up to about 5 mcg/ml.
The other fluorimetric method studied is specific for ampicillin. This involved the enhancement of fluorescence of inactivated product, aminobenzylpenicilloic acid of ampicillin by NaOH. It permits detection of less than 0.05 mcg/ml of ampicillin.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, 1987.
Keywords: Penicillin; Chemistry, Analytic